THE STUDIES OF WELLBEING, OPTIMAL MENTAL HEALTH AND FLOURISHING: CLARIFYING AND DIFFERENTIATING COMPLEX CONCEPTS - Barragán Estrada, Ahmad Ramsés (2023)
Backgrounds: this theoretical article reviews empirically and in detail the concepts of well-being, optimal/positive mental health, types of well-being and flourishing, with a view to clarification and differentiation based on what the current scientific literature offers, and given that they are often used as synonyms, or as interchangeable terms. State of the art: various criteria of inclusion and reference of what we usually consider "positive" and "negative" in scientific studies of well-being and distress (disease, pathogenic, decay) are explained and proposed as a framework and reliable guide for future research and work methodologies related to the constructs studied here, as well as a means of support in the elaboration and enrichment of the same definitions. In addition, specific and differentiated concepts of well-being, optimal mental health and flourishing, which are recognized as independent but interrelated, are proposed and articulated. Conclusions: the review of the literature and analysis of the information led to the emergence of a new concept called "integrative wellbeing", which seeks to compile the existing types of wellbeing and mental health that together are conducive to individual and social flourishing. Thus, we sought to have an impact on the use of adequate, current and functional terminology, due to the complexity and dynamism offered by the terms; trusting, in addition, that it will allow researchers and various professionals, the conformation and development of evaluation instruments, as well as possible practical applications in clinical, educational, social, political, labor or other fields.